On "Feedback stabilization of fed-batch bioreactors: Non-monotonic growth kinetics" - de Battista, Hernán (2005)
This note deals with the control of the substrate concentration in fed-batch bioreactions with non-monotonic growth kinetics. More specifically, a modified version of a linearizing control strategy is proposed. Its main advantage is that the implementation only requires the measurement of biomass concentration and the estimation (based on this measure) of the specific growth rate. Stability of the proposed control law is investigated.